Cosh ( + ) Cosh Cosh + Sinh Sinh + 2 + 2 + 2 2
Cosh ( + ) Cosh Cosh + Sinh Sinh + 2 + 2 + 2 2
Cosh ( + ) Cosh Cosh + Sinh Sinh + 2 + 2 + 2 2
𝑒 𝑥+𝑦 + 𝑒 −(𝑥+𝑦) 𝑥
𝑒 +𝑒
−𝑥 𝑦
𝑒 +𝑒
−𝑦 𝑥
𝑒 −𝑒
−𝑥 𝑦
𝑒 −𝑒
−𝑦
= ⋅ + ⋅
2𝑥 −𝑦 −𝑥 2 2 2 2
𝑒 𝑒 + 𝑒 𝑒 + 𝑒 𝑒 𝑦 + 𝑒 −𝑥 𝑒 −𝑦 + 𝑒 𝑥 𝑒 𝑦 − 𝑒 𝑥 𝑒 −𝑦 − 𝑒 −𝑥 𝑒 𝑦 + 𝑒 −𝑥 𝑒 −𝑦
𝑥 𝑦
=
4
2(𝑒 𝑥 𝑒 𝑦 + 𝑒 −𝑥 𝑒 −𝑦 ) 𝑒 𝑥+𝑦 + 𝑒 −(𝑥+𝑦)
= = .
4 2
Terbukti.
Catatan
cosh2 𝑥 − sinh2 𝑥 = 1
Cara lain
Turunan logaritmik.
𝐷𝑥 (sinh−1 (𝑥 + 1)) = 𝐷𝑥 ln (𝑢 + √𝑢2 + 1)
1
= 𝐷𝑥 (𝑢 + √𝑢2 + 1)
2
𝑢 + √𝑢 + 1
1 2𝑢
= ⋅1+
𝑢 + √𝑢2 + 1 2√𝑢2 + 1
1 1 𝑢
= + ⋅
𝑢 + √𝑢2 + 1 𝑢 + √𝑢2 + 1 √𝑢2 + 1
1 𝑢
= (1+ )
𝑢 + √𝑢2 + 1 √𝑢2 + 1
1 𝑢 + √𝑢2 + 1
= ⋅
𝑢 + √𝑢2 + 1 √𝑢2 + 1
1 1 1
= = = .
√𝑢2
+ 1 √(𝑥 + +1 1)2 + 2𝑥 + 2 √𝑥 2
(b) ∫ sinh(3𝑥 + 2) 𝑑𝑥
Misal 𝑈 = 3𝑥 + 2
𝑑𝑈 = 3𝑑𝑥
𝑑𝑈
𝑑𝑥 =
3
1 1
∫ sinh(𝑈)𝑑𝑈 = cosh(𝑈) + C
3 3
1
= cosh(3𝑥 + 2) + C.
3
ln 2
(d) ∫0 tanh(2𝑥 )𝑑𝑥
𝑑𝑈
Misal 𝑈 = 2𝑥; 𝑑𝑈 = 2𝑑𝑥; 𝑑𝑥 =
2
Untuk 𝑥 = 0; 𝑈 = 0, 𝑥 = ln 2; 𝑈 = 2 ln 2 ≈ 1,39
1 1,39
∫ tanh(𝑈)𝑑𝑈
2 0
Kita evaluasikan terlebih dahulu integral dari tanh(𝑈) dengan
memisalkan 𝑤 = cosh(𝑈), maka 𝑑𝑤 = sinh(𝑈)𝑑𝑈
sinh(𝑈) 1
∫ tanh(𝑈) 𝑑𝑈 = ∫ 𝑑𝑈 = ∫ 𝑑𝑤 = ln|𝑤| + C = ln | cosh(𝑈)| + C
cosh(𝑈) 𝑤
Kita kembali ke bentuk integral tentu.
1 1,39
∫ tanh(𝑈)𝑑𝑈
2 0
ln |cosh (𝑈)| 1,39
=[ ]0
2
ln |2,13| ln|1| ln|2,13|
≈[ − ]= ≈ 0,38 .
2 2 2
1
(e) ∫ sech2 (𝑥 − 2) 𝑑𝑥
1
𝑈=𝑥−
2
𝑑𝑈 = 𝑑𝑥
1
∫ sech2 𝑈 𝑑𝑈 = tanh(𝑈) + C = tanh (𝑥 − ) + C .
2